A Human-Computer Interaction System for Agricultural Tools Museum Based on Virtual Reality Technology - Ying Yang; Yiyi Fan; Ruizhi Sun (Advances in Multimedia)
Traditional museums and most digital museums use window display to exhibit their collections. However, the agricultural tools are distinctive for their use value and wisdom contained. Therefore, this paper first proposes a method of virtual interactive display for agricultural tools based on virtual reality technology, which combines static display and dynamic use of agricultural tools vividly showing the agricultural tools. To address the problems of rigid interaction and terrible experience in the process of human-computer interaction, four human-computer interaction technologies are proposed to design and construct a more humanized system including intelligent scenes switching technology, multichannel introduction technology, interactive virtual roaming technology, and task-based interactive technology. The evaluation results demonstrate that the system proposed achieves good performance in fluency, instructiveness, amusement, and practicability. This human-computer interaction system can not only show the wisdom of Chinese traditional agricultural tools to the experiencer all over the world but also put forward a new method of digital museum design.